Factors of Low Birth Weight (LBW) in Indonesia: An Analysis of the 2017 Indonesia Demographic and Health Survey (IDHS 2017) - Rahmadani, Haeda Dyah Masna; Puspitasantik, Yunita Dyah (Unnes Journal of Public Health, 2024)
Low birth weight (LBW) is one of the indicators of newborn mortality and also a health problem in infant growth and development. The case of LBW in Indonesia ranges from 5%-<10%, which makes Indonesia ranks sixth in Southeast Asia and in Indonesia as many as 1-3% of infant deaths occur. The aim of this study is to determine the factors associated with the case of LBW in Indonesia. This study used data from the 2017 Indonesian Demographic Health Survey (IDHS 2017) using a cross-sectional design. Analysis was conducted using descriptive analysis and followed by bivariate analysis with chi-square test and multivariate analysis using logistic regression. From the analysis results, factors that determined greater risk of LBW are lower economic status (p-value = 0.002; AOR = 2.026; 95% CI 1.292, urban residence (p-value = 0.012; AOR = 1.649; 95% CI 1.118-2.432), pregnancy complications (p-value = 0.011; AOR= 1.705; 95% CI (1.128-2.576), multiple pregnancy (p-value= 0.058; AOR= 4.405; 95% CI 0.954-20.344), and the opposite association with LBW case was the first child category pregnancy interval (p-value= 0.007; AOR= 0.605; 95% CI 0.421-0.870). The influencing factors of LBW case from this study were economic status, urban residence, pregnancy complications, and multiple pregnancies.